Contribuições para o plano de arborização da UTFPR – campus Medianeira - Lima, Adriely Faustino de (2024)
Urban afforestation is essential to create healthier and more livable cities, given that green areas play a fundamental role in improving the quality of life in modern cities, offering refuge from urban hustle and bustle, regulating temperature, conserving biodiversity and promoting physical and mental health. Therefore, careful planning and efficient management of urban trees are necessary. The Green Area Index (IAV), for example, is one of the tools that assist in planning, as it helps to quantify green areas in a region. Therefore, the study in question aimed to calculate the current IAV of UTFPR-MD, as well as search for new areas with arboreal potential within the Campus, to increase this index, in addition to searching for native species suitable for afforestation in the area. The study was developed with the help of Google Earth Pro and with certain information from UTFPR-MD, to carry out calculations and subsequent estimates on the local IAV, as for the selection of species native to the Atlantic Forest, these were chosen in the literature. At the end of the work, it was possible to verify that the Campus Green Area Index has 6.71 m² per inhabitant, which can be increased by another 3.29 m² as 6 other areas suitable for being planted with trees were detected, in addition to 15 native species suitable for afforestation.